Effects of high versus low-dose atorvastatin on high sensitive C-reactive protein in acute coronary syndrome - Zamani, Bijan (Niger Med J, 2014)
BACKGROUND: Cardiovascular disease is the leading cause of mortality. The previous findings which suggest the reduction in C-reactive protein (CRP) levels by statin encouraged us to conduct the present study in which we tested the effects of atorvastatin, on levels of hs-CRP in a prospective randomised clinical trial study on patients with acute coronary syndrome. MATERIALS AND METHODS: Present prospective randomised clinical trial study conducted on 180 patients who had developed coronary artery disease and presented in emergency departments of Educational-Medical centers of Tabriz University of Medical Sciences. The patients were divided randomly into two groups and then two therapeutic protocols were given to them. One group medicated by high-dose atorvastatin (40 mg) and the other group received low-dose atorvastatin (20 mg). All variables were collected by questionnaires and were analyzed. RESULTS: There were 180 patients consisted of 34 females and 56 males in low-dose atorvastatin group (L-DA group), and 30 females and 60 males in high-dose atorvastatin group (H-DA group) (P = 0.533). In this study atorvastatin in high doses decreased hs-CRP levels about 40% and in low doses it only caused decrease of 13.3%, and significant correlation was observed between two groups (Paired Sample T-test) (P = 0.001). Also atorvastatin in high doses decreased LDL levels about 23% and in low doses it only decreased 10%, and significant correlation was observed between two groups (Paired Sample T-test) (P = 0.001). Atorvastatin in high doses decreased HDL levels about 9% and in low doses it only decreased 6%, and again significant correlation was observed between two groups (P = 0.009). CONCLUSION: The present study confirms the novel observation that atorvastatin therapy results in a significant reduction in hs-CRP levels.